Nilai Moral dalam Novel Surat Kecil untuk Tuhan Karya Agnes Davonar - Usi Karundeng; Desi Sukenti (UIR Press, 2023)
The first moral action is based on the human heart itself. If the heart is dissatisfied with what it has, it will do what is right or what is wrong. This study uses a qualitative descriptive method, which is a research procedure with the results of presenting descriptive data in the form of the author's speech in the novel Small Letters for God. Based on the results of the discussion in this study, it can be concluded that the aspect of responsibility towards himself can be seen from the main character, namely Keke who is responsible for carrying out his duties both regarding education and regarding responsibility for his recovery. The aspect listed in moral values ​​is conscience. One of the characteristics of moral values ​​is that only these values ​​give rise to a